Preventive Efficacy, Safety, Immunogenic Activity, and Evaluation of Post-Vaccination Responses Following Immunization with Combined Trivalent Vaccine Vaktrivir (Measles-Rubella-Parotitis) in Premature Infants - Vadislav V. Semerikov; Nina O. Yаkobyuk; Lyudmila V. Sofronova; Nadezhda V. Yuminova; Natalia N. Vorobjeva; Nikolay A. Kontarov (Педиатрическая фармакология, 2024)
Background. Registration of combined trivalent vaccine Vaktrivir (measles-rubella-parotitis) in Russia necessitates studies on its preventive efficacy, safety, immunogenic activity, and post-vaccination responses following the immunization of premature infants. Objective. The aim of the study is to evaluate efficacy, safety, and immunogenic activity of combined trivalent vaccine (measles-rubella-parotitis) and level of post-vaccination responses following the immunization of premature infants. Methods. Experimental studies were conducted to evaluate safety, immunogenicity, and postvaccinal responses after immunization of premature infants with combined within prospective comparative clinical observation. Results. Administration of the combined trivalent vaccine Vaktrivir (measles-rubella-parotitis) in premature infants has shown: no cases of measles, rubella or parotitis among vaccinated persons within prospective clinical observation for 2 years; no disturbances in parameters of clinical blood analysis, biochemical blood count, total IgE, IgA, IgM, IgG (immunogram), or urine analysis among vaccinated children over time; no subjective perceptions, adverse events signs at physical examination among vaccinated compared to baseline parameters; low post-vaccination reactions (6.7%) and similar tolerance of trivalent vaccine Vaktrivir among full-term infants (3.3%) (p = 0.301). Conclusion. Administration of the combined trivalent vaccine Vaktrivir (measles-rubella-parotitis) in premature infants has demonstrated high safety profile and immunogenic properties for measles, rubella and parotitis components, good tolerability, and low post-vaccination responses after immunization, comparable to vaccination of full-term infants.